Field reports form for submitting seasonal observations of Iowa birds, Jan L. Walter, summer 1993 - Walter, Jan L.et al (1993)
Summer report of birds found in northern Iowa contributed by Jan L. Walter. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of summer 1993. Plustek - flatbed